2018
DOI: 10.1002/jaba.431
|View full text |Cite
|
Sign up to set email alerts
|

The role of signals in two variations of differential‐reinforcement‐of‐low‐rate procedures

Abstract: Differential-reinforcement-of-low-rate (DRL) schedules are used to decrease the overall rate of, but not eliminate, a target response. Two variations of DRL, spaced-responding and full-session, exist. Preliminary comparative analyses suggest that the two schedules function differently when unsignaled. We compared response rates under these two DRL variations with and without signals. In Experiment 1, five preschool students played a game in which points were earned under DRL schedules. In some sessions, a stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Incorrect responses, such as throwing away bottle or paper items, reset the VR schedule. The "trash" receptacle had no bag or was "open" (similar to the S+ shown in Figure 1 of Becraft et al, 2018). • Extinction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Incorrect responses, such as throwing away bottle or paper items, reset the VR schedule. The "trash" receptacle had no bag or was "open" (similar to the S+ shown in Figure 1 of Becraft et al, 2018). • Extinction.…”
Section: Methodsmentioning
confidence: 99%
“…For the DRL comparison phases (second and fourth phase of each panel in Figure 1), we compared response rates in the two DRL conditions (i.e., full-session, spaced-responding) to each other, as well as to the optimal or allowable rate (i.e., 50% of responding in the last VR session of the first baseline phase hereafter referred to as baseline). 1 In keeping with Becraft et al (2018), we defined "near" optimal or allowable as between 25% and 75% reduction from baseline responding.…”
Section: Drl Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when instructions were given, they accurately spaced their responses in both conditions, with a mean proportion of reinforced IRTs over .60. Becraft et al () measured DRL in children aged 4 to 5 years and they also compared temporal adjustment when a visual signal indicated the availability of the reinforcer. The results indicated that the proportions of reinforced IRTs were over .40 when the signals were present and dropped to less than .25 when they were absent.…”
mentioning
confidence: 99%